Impact of pesticide residues (chlorpyrifos, cypermethrin, profenophos) on health and liver marker values alkaline phosphate (ALP), alanine amino transferase (ALT) and (AST) among workers of pesticide formulation & packing plants in Pakistan - Sumera Saghir, Muhammad Shahroz Humza, Sana Sarmad, Shama Akram, Muhammad Fahim ul Haq (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the impact of pesticide residues (chlorpyrifos, cypermethrin, profenophos) on health and liver marker values alkaline phosphate (ALP), aspartate amino transferase (AST) and alanine amino transferase (ALT) among workers of pesticide formulation & packaging plants in Pakistan Materials and Methods: A hundred workers of the age group between 20-50 years working, for at least a year, at various pesticide formulation & packaging units were included in the present study. One hundred workers, apparently healthy, with no history of pesticide exposure - after matching age, sex and social status - were taken as control. Biochemical tests ALP, AST and ALT, were carried out using chemistry autoanalyzer, Dimension RXL (Dade Behring). Pesticide residues (chlorpyrifos, cypermethrin, profenophos) were carried out employing gas chromatograph electron capture detector GCECD 2010, Shimadzu Japan. Results: In current study 100 workers of pesticide industry were taken and ALP, AST and ALT of 80 workers out of 100 were found to be within the normal limits. However, 20 workers had unusually raised levels of ALP ALT and AST. These twenty workers showed pesticide residues of chlorpyrifos, cypermethrin, profenopos in their blood. Conclusions: the pesticide residual level of all the workers were very low (below the no observable adverse affect level NOAEL) and were not too significant to create health problems.